Cairn Burial of the historical period around Khansaar dam, Toujerdi district of Fars province, Iran - KHANIPOUR, Morteza; MOLAEI KORDSHOULI, Hamed (Historia i Świat, 2023)
In the historical period, the Fars region in Iran was one of the most important cultural areas in the world, and it is considered the origin of the ancient Achaemenid and Sasanian empires. Although some areas of Sarchahan county have been studied well, no archaeological survey has been conducted there until the construction of Khansaar Dam and rescue operations in its area. As part of an archaeological survey in the Toujerdi district of Sarchahan county, 92 cairn burials were found. According to the survey conducted in five areas around Khansaar Dam, the distribution of cairn burials, commonly known as Khereftkhaneh, has been identified. From Pakistan to the west of Iran, this type of burial method can be observed, and the burials of Toujerdi region can be considered associated with burials from the Parthian and Sasanian periods.